Pelatihan Pembuatan Cairan Serbaguna Ecoenzym Bagi Anggota Kelompok Wanita Kristen GKI Getsemani Kotaraja Jayapura, Papua - Henderina J. Keiluhu; Elieser Elieser; Yogi S. Saputra; Rachel Awi; Marisa C. Rumpampam; Maria M. Babaubun (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Eco enzymes are versatile liquids made from fermented fruit peels which have many benefits in everyday life. This training is a community service activity that was held on 23 May â€“ 23 August 2022, with the aim of providing practical knowledge about the benefits of eco enzymes and practicing making eco enzymes. As many as 16 women participants who are members of the Christian Women's Fellowship from Wyk 4 GKI Getsemani Kotaraja Jayapura took part in this activity. The method used is participatory socialization and class action accompanied by evaluation. The results of this training showed that the success rate of outreach to participants reached 68.75%, with a final test score of 79.38%. In general, the participants were able to produce their own eco enzyme liquid which had been fermented for three months and experienced its benefits as a multipurpose liquid, namely as a floor cleaning fluid.Keyword: Ecoenzyme; training; GKI Getsemani Kotaraja; Jayapura.Â